Work Discipline as a Strategic Mediator Linking Islamic Leadership, Religiosity, and HR Performance in Competitive Islamic Economic Organizations - Ardiani Ika Sulistyawati; Ericke Fridatien; Vensy Vydia; Aprih Santoso; Ammeruddin Shah Suboh (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
This study investigates the mediating role of work discipline in the relationship between Islamic Leadership, religiosity, work motivation, and human resource (HR) performance within Islamic educational institutions. A quantitative explanatory research design was employed to examine causal relationships among the constructs under study. The population consisted of teachers at State Islamic High School Semarang, Indonesia, and data were collected using saturated sampling, a non-probability technique in which the entire accessible population is used as respondents. A total of 60 teachers participated by completing a structured questionnaire measured on a five-point Likert scale. Instrument reliability and validity were assessed through Cronbach's alpha, composite reliability, and convergent validity indicators. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), which is appropriate for small sample sizes, complex mediation models, and non-normal data structures. The results reveal that work discipline significantly mediates the effect of Islamic Leadership on HR performance, as indicated by a higher indirect effect value (9.558 > 2.247). A similar pattern is observed in the relationship between religiosity and HR performance, where the indirect effect (11.158 > 5.066) exceeds the direct impact. Moreover, work discipline is found to mediate the influence of work motivation on HR performance, supported by a more substantial indirect effect (15.474 > 0.801). Overall, the findings highlight work discipline as a critical mechanism that strengthens HR performance in Islamic institutional settings.